Impact of formation water on the generation of H2S in condensate reservoirs： a case study from the deep Ordovician in the Tazhong Uplift of the Tarim Basin, NW China - Su, Jin; Wang, Yu; Wang, Xiao-Mei; He, Kun; Yang, Hai-Jun; Wang, Hui-Tong; Wang, Hua-Jian; Zhang, Bin; Huang, Ling; Weng, Na; Bi, Li-Na; Xiao, Zhi-Hua (Petroleum science, 2017)
A number of condensate reservoirs with high concentrations of H2S have been discovered in the deep dolomite reservoirs of the lower Ordovician Yingshan Formation（O1y） in the Tazhong Uplift, where the formation water has a high p H value. In the O1y reservoir, the concentrations of Mg^2＋ and SO4^2-in the formation water are higher than those in the upper Ordovician formation.The concentration of H2 S in the condensate reservoirs and the concentration of Mg^2＋in the formation water correlate well in the O1y reservoirs of the Tazhong Uplift, which indicates a presumed thermochemical sulfate reduction（TSR） origin of H2S according to the oxidation theory of contact ion-pairs（CIPs）. Besides, the p H values of the formation water are positively correlated with the concentration of H2S in the condensate reservoirs, which may indicate that high p H might be another factor to promote and maintain TSR. Oil–source correlation of biomarkers in the sulfuretted condensates indicates the Cambrian source rocks could be the origin of condensates. The formation water in the condensate reservoirs of O1y is similar to that in the Cambrian; therefore, the TSR of sulfate-CIPs likelyoccurred in the Cambrian. High H2S-bearing condensates are mainly located near the No. 1 Fault and NE-SW strikeslip faults, which are the major migration pathway of deep fluids in the Tazhong Uplift. The redox between sulfateCIPs and hydrocarbons is the generation mechanism of H2S in the deep dolomite condensate reservoirs of the Tazhong Uplift. This finding should be helpful to predict the fluid properties of deep dolomite reservoirs.